RSA Security's Official Guide to Cryptography: Keller Graduate School of Management of DeVry University - Steve Burnett (MC Graw Hill, 2004)
File dalam bentuk Gambar, Video (AVI), Internet (Htm), Visual Basic, dll; Isi: Common (Graphics, Help, Redist, Tools, dan Wizard 98), DCOM98, FP98EXT, HTMLHELP, IE4, NTSP3, OS, SETUP, SHARED, VB98, dll; Judul Dalam Kemasan.